1967
DOI: 10.1042/bj1040369
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and stereospecificity of α-chymotrypsin

Abstract: 1. The optically pure p-nitrophenyl esters of the d and l enantiomers of N-acetyl-tryptophan, N-acetylphenylalanine and N-acetyl-leucine, and the p-nitrophenyl ester of N-acetylglycine, have been prepared. 2. These materials are all substrates of alpha-chymotrypsin, and the rates of deacylation of the corresponding acyl-alpha-chymotrypsins have been determined. 3. As the size of the amino acid side chain increases, the l series deacylate progressively faster than the N-acetylglycyl-enzyme, and the d series pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1970
1970
1985
1985

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…Similar constraint of a small molecule has been shown to increase a reaction rate by 5 X 104 (75). The ratio of deacylation rates of N-acetyltryptophanyl chymotrypsin compared to its glycyl analogue is 560 (76). This seems to be primarily an entropic effect, due to the orientating effect of the tryptophanyl group.…”
Section: Enzyme Catalysismentioning
confidence: 76%
“…Similar constraint of a small molecule has been shown to increase a reaction rate by 5 X 104 (75). The ratio of deacylation rates of N-acetyltryptophanyl chymotrypsin compared to its glycyl analogue is 560 (76). This seems to be primarily an entropic effect, due to the orientating effect of the tryptophanyl group.…”
Section: Enzyme Catalysismentioning
confidence: 76%
“…The results obtained at pH 8.8 were less unequivocal. A more definite indication of hydrolysis might be expected with an ester having a better leaving group such as thep-nitrophenoxide ion ; however, phenylalanine g-nitrophenyl ester is very unstable in aqueous solution and its hydrolysis is For neutral esters of ~-phenylpropionic acid derivatives, Ingles and Knowles (36,37) found that the -NHof the a-acetamido group was necessary to achieve maximum stereospecificity in the catalytic step subsequent to the binding stage. The 'free' amino acid esters can achieve the same degree of stereospecificity without the interaction of the -NH-(which is now believed to be H bonded to a main-chain carbonyl (38)).…”
Section: Steaesspec~~citymentioning
confidence: 97%
“…Enzymes showing stereospecificity toward the aminoacyl residue interact with this residue a t least a t two loci [27]. With peptidyl transferase this condition is met by the binding site for the side chain of the amino acid residue and some other site, such as that for binding the 2'-OH group of ribose as was discussed in a previous paper [13].…”
Section: Products Of the L'ransfer Reactimmentioning
confidence: 99%